PETA PERKEMBANGAN LEKSIKOGRAFI ARAB DI INDONESIA: STUDI KRITIS ATAS KAMUS KARYA MAHMUD YUNUS - Abdul Wahab, Muhbib (Arabi : Journal of Arabic Studies, 2017)
This critical study is aimed to explain the position of Arabic-Indonesian dictionary (the work of Mahmud Yunus) in the mapping of Arabic lexicography development in Indonesia. This study was carried out through bibliographical based qualitative with the work of Mahmud Yunus as the main source. The results indicate that Mahmud Yunus Dictionary is categorized into bilingual dictionary following the sarfi alifbai system, in which the entry and vocabulary are systemized alphabetically. The display of the dictionary is a bland of common dictionary and pictorial dictionary, because the dictionary is provided with pictures adapted from al-Munjid. The critical and substantive evaluation study show that the compiling process of the dictionary is not fully based on lexicology and modern linguistics. Some mistakes (such as printing, diction, meaning, and entry), pictures, and classic illustrations, and some involvement of the ammiyyah vocabularies should be revised and contextualized in accordance to the development of science and technology. This study need to be developed to make the dictionary contribute the development of Arabic language teaching.